2015
DOI: 10.5539/jas.v7n5p118
|View full text |Cite
|
Sign up to set email alerts
|

Rooting of Camu-Camu (Myrciaria dubia) in Different Propagation Systems and Reproductive Phases

Abstract: Closed environment and controlled irrigation techniques are conventionally used to root camu-camu stem cuttings. But development of other techniques of camu-camu propagation is required for smallholder growers in Peru, who cultivate camu-camu on restingas, old river levee fragments on the margins of white-water rivers. Additionally, the month in which cuttings are collected from camu-camu restingas plantations could influence their rooting capacity, influencing the effectiveness at the propagation bed stage. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Santana (2009) and Delgado & Yuyama (2011) mention that cuttings with high rooting index, but without sprouts, do not guarantee the plant propagation. NS was higher than numbers reported by other authors, who worked with camu-camu propagation by cuttings (Oliva, 2005a;2005b;Galucio, 2002, Yuyama, 2002Santana, 2009;Delgado & Yuyama, 2011& Delgado et al, 2015.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Santana (2009) and Delgado & Yuyama (2011) mention that cuttings with high rooting index, but without sprouts, do not guarantee the plant propagation. NS was higher than numbers reported by other authors, who worked with camu-camu propagation by cuttings (Oliva, 2005a;2005b;Galucio, 2002, Yuyama, 2002Santana, 2009;Delgado & Yuyama, 2011& Delgado et al, 2015.…”
Section: Resultsmentioning
confidence: 53%
“…"Propagation by cuttings has been the most used method for the maintenance of the genetic characteristics of the stock plants, aiming at uniformity, size reduction and precocity" (Hartmann et al, 2011). "Although many studies have shown satisfactory results with this propagation method in camu-camu, together with growth regulators, there are no reports regarding the genotype influence on the rooting capacity of the species" (Galucio, 2002;Yuyama, Aguiar & Yuyama, 2002;Cruz, 2005aCruz, , 2005bSantana, 2009;Delgado & Yuyama, 2010;Delgado et al, 2015).…”
Section: Referenciasmentioning
confidence: 99%
“…Santana (2009) and Delgado & Yuyama (2011) mention that cuttings with high rooting index, but without sprouts, do not guarantee the plant propagation. NS was higher than numbers reported by other authors, who worked with camu-camu propagation by cuttings (Oliva, 2005a;2005b;Galucio, 2002, Yuyama, 2002Santana, 2009;Delgado & Yuyama, 2011& Delgado et al, 2015.…”
Section: Resultsmentioning
confidence: 53%
“…"Propagation by cuttings has been the most used method for the maintenance of the genetic characteristics of the stock plants, aiming at uniformity, size reduction and precocity" (Hartmann et al, 2011). "Although many studies have shown satisfactory results with this propagation method in camu-camu, together with growth regulators, there are no reports regarding the genotype influence on the rooting capacity of the species" (Galucio, 2002;Yuyama, Aguiar & Yuyama, 2002;Cruz, 2005aCruz, , 2005bSantana, 2009;Delgado & Yuyama, 2010;Delgado et al, 2015).…”
Section: Referenciasmentioning
confidence: 99%
See 1 more Smart Citation